2008
DOI: 10.1063/1.2884530
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic luminance loss in phosphorescent small-molecule organic light emitting devices due to bimolecular annihilation reactions

Abstract: Operational degradation of blue electrophosphorescent organic light emitting devices (OLEDs) is studied by examining the luminance loss, voltage rise, and emissive layer photoluminescence quenching that occur in electrically aged devices. Using a model where defect sites act as deep charge traps, nonradiative recombination centers, and luminescence quenchers, we show that the luminance loss and voltage rise dependence on time and current density are consistent with defect formation due primarily to exciton-pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
193
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 345 publications
(200 citation statements)
references
References 26 publications
5
193
2
Order By: Relevance
“…It has been suggested that the intrinsic degradation of blue PHOLEDs results from energetically driven formation of traps 16,17 that can quench excitons and also act as non-radiative charge recombination centres. These traps are formed due to bimolecular triplet-polaron annihilation (TPA) where energy is transferred from triplets to polarons (that is, charged molecules).…”
mentioning
confidence: 99%
“…It has been suggested that the intrinsic degradation of blue PHOLEDs results from energetically driven formation of traps 16,17 that can quench excitons and also act as non-radiative charge recombination centres. These traps are formed due to bimolecular triplet-polaron annihilation (TPA) where energy is transferred from triplets to polarons (that is, charged molecules).…”
mentioning
confidence: 99%
“…Models and experiments [11,13] have unambiguously attributed the OPV ageing process to the formation of defects in the active region due to exciton-induced molecular decomposition, analogous to the mechanism of Giebink et al for PHOLEDs discussed above [3]. In fullerene-based OPVs, however, the exciton itself promotes the formation of higher order oligomers [12] of C 60 (e.g.…”
Section: Operating Lifetime Of Organic Photovoltaicsmentioning
confidence: 99%
“…This finding has been universally observed and is independent of the choice of phosphor or conductive host molecules, suggesting that the cause is of fundamental rather than purely extrinsic origin. This led to a study by Giebink et al [3] that showed that the long-term deterioration of luminance was due to an energy-driven Auger-like process shown in figure 1, whereby an electrically generated triplet exciton on the phosphor encounters a charge (polaron) on a nearby host molecule [4]. The collision results in the de-excitation of the exciton, momentarily promoting the polaron to a very high energy in excess of 7 eV in blue OLEDs where it has a significant probability of engaging in a dissociative reaction with the molecule (most likely the host, in the case studied by Giebink et al).…”
Section: Operating Lifetime Of Blue Pholedsmentioning
confidence: 99%
See 2 more Smart Citations